Late glacial and Holocene climate variability, southernmost Patagonia. (1st February 2020) - McCulloch, Robert D.; Blaikie, James; Jacob, Barbara; Mansilla, Claudia A.; Morello, Flavia; De Pol-Holz, Ricardo; San Román, Manuel; Tisdall, Eileen; Torres, Jimena
Abstract: A Late glacial – Holocene palaeoecological record, constrained by a robust chronology, from a peat bog near Punta Burslem (54°54′S, 67°57′W) on Isla Navarino, southernmost Patagonia documents the shifts in intensity and focus of the Southern Westerly Winds (SWWs) at these high latitudes. Such long-term records are required to reconstruct and better understand the likely regional impacts of a poleward shift and intensification of the SWWs predicted under global warming scenarios. Deglaciation at Punta Burslem occurs sometime before c. 17, 000 cal a BP, and the post glacial landscape is dominated by cold tolerant pioneer species. Nothofagus woodland is established by c. 12, 250 cal a BP, this moisture sensitive vegetation type retreats in the early to mid-Holocene from c. 9700 to 7050 cal a BP reflecting an intense and sustained drier phase associated with a prolonged poleward contraction of the SWWs. After c. 6000 cal a BP there is a regional trend to cooler and wetter climate. However, we identify at least five periods of rapid climate change (RCC) leading to drier conditions at this southern extreme of Patagonia: c. 5350-4750 cal a BP, c.4300-3300 cal a BP, c. 2600-1850 cal a BP, c. 1350-1100 cal a BP and c. 550-350 cal a BP. From a synthesis of our Isla Navarino records and a latitudinal spread (34°-64°S) of multiproxy records it is proposed that these periods of RCC and relatively drier conditions indicate latitudinal shifts in the location and intensity of the SWWs in response to climatic warming leading to reduced precipitation at the southern margins of Patagonia. Highlights: A new Late glacial-Holocene palaeoenvironmental record from Isla Navarino. Sustained drier period during the early Holocene between c.9.7 and c. 6.0 ka. Increased humidity punctuated by drier periods during the mid-to late-Holocene. A latitudinal synthesis of records from ∼34° to 64°S describes shifts of the SWWs. Demonstrates pollen preservation as a robust index of climate change.